2016
DOI: 10.1038/srep18850
|View full text |Cite
|
Sign up to set email alerts
|

Automatic stage identification of Drosophila egg chamber based on DAPI images

Abstract: The Drosophila egg chamber, whose development is divided into 14 stages, is a well-established model for developmental biology. However, visual stage determination can be a tedious, subjective and time-consuming task prone to errors. Our study presents an objective, reliable and repeatable automated method for quantifying cell features and classifying egg chamber stages based on DAPI images. The proposed approach is composed of two steps: 1) a feature extraction step and 2) a statistical modeling step. The egg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
75
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 55 publications
1
75
2
Order By: Relevance
“…While an earlier study failed to detect a bias in the orientation of planar cell divisions, developmental stage was not accounted for in that work (Alégot et al, 2018). We determined egg chamber stage by calculating volume, with adjustments based on nuclear staining pattern, and by defining the switch between 6 and 7 as the cessation of follicle cell mitoses (Klusza & Deng, 2011;Jia et al 2016;Ng et al, 2016). We next considered whether the bias in division orientation is driven by egg chamber shape change.…”
Section: Planar Division Orientation In the Follicular Epithelium Is mentioning
confidence: 99%
See 1 more Smart Citation
“…While an earlier study failed to detect a bias in the orientation of planar cell divisions, developmental stage was not accounted for in that work (Alégot et al, 2018). We determined egg chamber stage by calculating volume, with adjustments based on nuclear staining pattern, and by defining the switch between 6 and 7 as the cessation of follicle cell mitoses (Klusza & Deng, 2011;Jia et al 2016;Ng et al, 2016). We next considered whether the bias in division orientation is driven by egg chamber shape change.…”
Section: Planar Division Orientation In the Follicular Epithelium Is mentioning
confidence: 99%
“…We tested this possibility by disrupting Fat2 (previously Kugelei), which is required for egg chamber rotation (Viktorinová et al, 2009;Cetera et al, 2014). We determined egg chamber stage by calculating volume, with adjustments based on nuclear staining pattern, and by defining the switch between 6 and 7 as the cessation of follicle cell mitoses (Klusza & Deng, 2011;Jia et al 2016;Ng et al, 2016). Using this method, we found that Fat2-shRNA egg chambers are modestly, but significantly, less elongated than wild-type egg chambers at stage 6 (Figs 4C and EV2G and H).…”
Section: Planar Division Orientation In the Follicular Epithelium Is mentioning
confidence: 99%
“…A) Schematic showing the timeline of oocyte development [48, 49]. B) Nondisjunction in c(2)M − ; UASp-c(2)M 3XHA /hs-Gal4 females measured following 1 hour of heat shock and the number of days indicated within each bar.…”
Section: Figurementioning
confidence: 99%
“…Samples were washed 5× and TUNEL-stained using the Roche In Situ Cell Death Detection Kit, TMR Red according to the manufacturer's protocol. Egg staging was performed as described by Wijesekera et al (56). Ovaries of virgin day 5 females of indicated genotype were raised individually in isolation vials, dissected in PBS, and 10 mature, stage 14 oocytes were collected from 10 sample flies.…”
mentioning
confidence: 99%